2004
DOI: 10.1016/s1567-1356(03)00205-8
|View full text |Cite
|
Sign up to set email alerts
|

Expression analysis of the lipase gene family during experimental infections and in patient samples

Abstract: Secreted lipases of Candida albicans are encoded by a gene family with at least 10 members (LIP1-LIP10). The expression pattern of this multigene family was investigated using reverse transcription polymerase chain reaction in experimental infections and in samples of patients suffering from oral candidosis. The findings illustrate that individual lipase genes are differentially regulated in a mouse model of systemic candidosis with some members showing sustained expression and others being transiently express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
86
0
4

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(92 citation statements)
references
References 30 publications
2
86
0
4
Order By: Relevance
“…Thus, in the host, SAP4, SAP5 and SAP6 show distinctive patterns of expression. Differential expression of LIP genes, encoding a family of secreted lipases, has also been demonstrated in host samples [34,35] and in laboratory growth [36]. Thus, one way that C. albicans ensures that a SAP gene will be expressed when needed for infection in different host niches is through differential expression of a large family of Sap isozymes.…”
Section: Niche Specific Genetic Responses To the Hostmentioning
confidence: 99%
“…Thus, in the host, SAP4, SAP5 and SAP6 show distinctive patterns of expression. Differential expression of LIP genes, encoding a family of secreted lipases, has also been demonstrated in host samples [34,35] and in laboratory growth [36]. Thus, one way that C. albicans ensures that a SAP gene will be expressed when needed for infection in different host niches is through differential expression of a large family of Sap isozymes.…”
Section: Niche Specific Genetic Responses To the Hostmentioning
confidence: 99%
“…albicans is known to have 10 lipase encoding genes, one (LIP1) characterized by Fu et al [44] and nine (LIP2-LIP10) by Hube et al [31]. Further examinations of C. albicans lipases revealed that individual genes are regulated differently during an infection and gene expression of each ORF was mainly dependent upon the stage of infection [45]. Interestingly, the different genes had variable contributions to virulence.…”
Section: Function Of Fungal Secreted Lipasesmentioning
confidence: 99%
“…Interestingly, the different genes had variable contributions to virulence. The role of LIP5 and LIP8 in C. albicans virulence was highlighted as their expression levels remained the highest when examining isolates recovered from systemically infected mice or from human oral specimens [45]. Furthermore, the generation of a C. albicans strain lacking LIP8 led to experiments demonstrating that this null mutant was less virulent in vivo compared to wild-type [46].…”
Section: Function Of Fungal Secreted Lipasesmentioning
confidence: 99%
“…et al, 2006;STEHR et al, 2004;ZAKIKHANY et al, 2007 HOYER et al, 2008;NOBILE et al, 2006a;NOBILE et al, 2006b;RICICOVA et al;ZHAO et al, 2006), e que as proteínas Als1p/Als3p e Hwp1 assumem papéis complementares na formação de biofilme (NOBILE et al, 2008 Estudos anteriores demonstraram que alguns substratos como RHE, siliconas para cateter, ou mesmo resinas acrílicas para dentaduras são modelos válidos para o estudo de biofilmes de C. albicans; e a expressão dos genes HWP1 e genes da família ALS, entre outros, foi avaliada em superfícies bióticas e superfícies abióticas (GREEN et al, 2004;NAGLIK et al, 2008;SAMARANAYAKE, Y.H. et al, 2006;STEHR et al, 2004;ZAKIKHANY et al, 2007).…”
Section: Discussionunclassified